Spunbond nonwoven fabric, method for manufacturing the same, and packaging material

JP2026165682APending Publication Date: 2026-10-14TORAY INDUSTRIES INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025058201
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

Smart Images

  • Figure 2026165682000001
    Figure 2026165682000001
Patent Text Reader

Abstract

Provided are a nonwoven fabric excellent in heat seal processability and mechanical strength, and a packaging material using the same. [Solution] A spunbonded nonwoven fabric composed of core-sheath type composite fibers, wherein the core component of the core-sheath type composite fibers is a thermoplastic resin A containing a polyester-based resin as a main component, the sheath component of the core-sheath type composite fibers is a thermoplastic resin B containing a polyolefin-based resin as a main component, and in differential scanning calorimetry measurement of the spunbonded nonwoven fabric, there is a single melting peak derived from the polyolefin-based resin, and the following formulas 1 and 2 are satisfied. 0.10≦P C1 ≦0.70 ···(Formula 1) 0.10≦P C2 -P C1 ≦0.55 ···(Formula 2) P C1 is the area ratio (no unit) of the core component in the cross section of the core-sheath type composite fiber in the portion on one surface side of the spunbonded nonwoven fabric, and P C2 is the area ratio (no unit) of the core component in the cross section of the core-sheath type composite fiber in the portion on the other surface side of the spunbonded nonwoven fabric.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to spunbond nonwoven fabric, a method for producing the same, and packaging materials. [Background technology]

[0002] In recent years, nonwoven fabrics have been used in a variety of applications, including industrial materials, civil engineering materials, construction materials, consumer goods, agricultural materials, packaging materials, sanitary materials, and medical materials.

[0003] In particular, nonwoven fabrics made of core-sheath composite fibers, in which a high-melting-point polymer is arranged in the core and a low-melting-point polymer in the sheath, have excellent heat-sealing properties and are suitable for use in bags and other applications. However, using such core-sheath composite fibers can cause problems during heat sealing, such as some of the molten polymer from the sheath fusing to the crimping part of the bag-making machine, causing processing troubles, or the fused polymer accumulating in the crimping part and adhering to the bag, thus reducing the quality of the product. [Prior art documents] [Patent Documents]

[0004] [Patent Document 1] Japanese Patent Publication No. 2007-321311 [Overview of the project] [Problems that the invention aims to solve]

[0005] Patent Document 1 proposes laminating a nonwoven web layer on one side of a heat-sealable nonwoven web layer composed of core-sheath composite fibers in which a high-melting-point polymer is arranged in the core and a low-melting-point polymer is arranged in the sheath, with a nonwoven web layer composed of fibers in which a polymer having a higher melting point than the low-melting-point polymer arranged in the sheath of the core-sheath composite fiber is arranged at least on the surface of the fibers.

[0006] However, because two types of fiber webs with different melting points in the sheath are laminated, the nonwoven fabric can become over-adhered, reducing its strength, or delamination between the nonwoven fabric layers can easily occur.

[0007] Therefore, the object of the present invention is to provide a nonwoven fabric with excellent heat-sealability and mechanical strength, and a packaging material made using the same. [Means for solving the problem]

[0008] The present invention and its preferred embodiments are shown below. [1] A spunbond nonwoven fabric composed of core-sheath composite fibers, wherein the core component of the core-sheath composite fiber is a thermoplastic resin A mainly composed of polyester resin, and the sheath component of the core-sheath composite fiber is a thermoplastic resin B mainly composed of polyolefin resin, and when differential scanning calorimetry is performed on the spunbond nonwoven fabric, there is a single melting peak originating from the polyolefin resin, and furthermore, the following equations 1 and 2 are satisfied. 0.10≦P C1 ≦0.70 (Formula 1) 0.10≦P C2 -P C1 ≦0.55 (Equation 2). Here, P C1 This is the area ratio (unitless) of the core component in the cross-section of the core-sheath type composite fiber in the portion of one surface side of the spunbond nonwoven fabric, P C2 This is the area ratio (unitless) of the core component in the cross-section of the core-sheath type composite fiber in the other surface portion of the spunbond nonwoven fabric. [2] The spunbond nonwoven fabric according to [1], wherein the polyester resin is polyethylene terephthalate resin, the polyolefin resin is polyethylene resin, and the difference between the temperature of the melting peak with the largest melting heat and the temperature of the melting peak with the second largest melting heat detected when differential scanning calorimetry is performed on the spunbond nonwoven fabric is 50°C or more and 250°C or less. [3] The apparent density of the spunbond nonwoven fabric is 0.10 g / cm 3 or more and 0.90 g / cm 3 or less, the spunbond nonwoven fabric according to [1] or [2]. [4] The product of tensile strength and elongation per unit basis weight in the longitudinal direction of the spunbond nonwoven fabric is 1.0 (N / 50mm) / (g / m 2 ) or more and 4.0 (N / 50mm) / (g / m 2 ) or less, the spunbond nonwoven fabric according to any one of [1] to [3]. [5] A method for producing the spunbond nonwoven fabric according to any one of [1] to [4], the method comprising: a step of forming a first fiber web composed of first core-sheath type composite fibers, wherein the core component is a thermoplastic resin containing a polyester-based resin as a main component, and the sheath component is a thermoplastic resin containing a polyolefin-based resin as a main component; a step of forming a second fiber web composed of second core-sheath type composite fibers on the first fiber web, wherein the core component is a thermoplastic resin containing a polyester-based resin as a main component, and the sheath component is a thermoplastic resin containing a polyolefin-based resin as a main component, so as to form a laminated web; and a step of thermally fusing the laminated web with a pair of heat rolls, to obtain a spunbond nonwoven fabric satisfying the following formulas 1 and 2, the method for producing a spunbond nonwoven fabric 0.10≦P C1 ≦0.70 ···(Formula 1) 0.10≦P C2 -P C1 ≦0.55 ···(Formula 2). Herein, P C1 is the area ratio (no unit) of the core component in the cross section of the core-sheath type composite fiber in the portion on one surface side of the spunbond nonwoven fabric, P C2 is the area ratio (no unit) of the core component in the cross section of the core-sheath type composite fiber in the portion on the other surface side of the spunbond nonwoven fabric. [6] The polyolefin-based resin is a polyethylene-based resin, and the solid density of the polyethylene-based resin is 0.935 g / cm 3 or more and 0.970 g / cm 3The method for producing a spunbond nonwoven fabric as described in [5] is as follows: [7] Packaging material containing a spunbond nonwoven fabric as described in any of [1] to [4]. [Effects of the Invention]

[0009] According to the present invention, a spunbond nonwoven fabric with excellent heat-sealability and mechanical strength, and a packaging material using the same can be obtained. [Modes for carrying out the invention]

[0010] The spunbond nonwoven fabric of the present invention is a spunbond nonwoven fabric composed of core-sheath type composite fibers, wherein the core component of the core-sheath type composite fiber is a thermoplastic resin mainly composed of polyester resin, and the sheath component of the core-sheath type composite fiber is a thermoplastic resin mainly composed of polyolefin resin.

[0011] The components of the present invention will be described in detail below, but the present invention is not limited in any way to the scope described below, as long as it does not exceed the gist of the invention.

[0012] [Thermoplastic resin A] The fibers constituting the spunbond nonwoven fabric of the present invention contain a thermoplastic resin A, mainly composed of a polyester resin, as a constituent component. This allows for the production of a spunbond nonwoven fabric with sufficient strength and rigidity for practical use. In this invention, "polyester resin" refers to various polyester resins such as polyethylene terephthalate (described later), mixtures thereof, copolymers, and resins to which additives have been added. Hereafter, unless otherwise specified, the same applies to any mention of "...-type resin."

[0013] Polyester resins primarily consist of high-molecular polymers composed of acid and alcohol components as monomers. In this invention, "primarily consisting of..." means that the mass ratio of the said component to the total mass is greater than 50% by mass. Hereafter, unless otherwise specified, the same applies to any description of "primarily consisting of...".

[0014] As acidic components, aromatic carboxylic acids such as phthalic acid (ortho form), isophthalic acid, and terephthalic acid, aliphatic dicarboxylic acids such as adipic acid and sebacic acid, and alicyclic dicarboxylic acids such as cyclohexanecarboxylic acid can be used. As alcoholic components, ethylene glycol, diethylene glycol, and polyethylene glycol can be used.

[0015] Examples of polyester resins include polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polytrimethylene terephthalate (PTT), polyethylene naphthalate (PEN), polylactic acid (PLA), and polybutylene succinate (PBS). Among these, PET is preferred because it has a high melting point, excellent heat resistance, and also possesses excellent strength and rigidity.

[0016] The thermoplastic resin A used in the present invention preferably contains 70% by mass or more of the above-mentioned polyester resin. Preferably, by containing 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more of the polyester resin, a spunbond nonwoven fabric with excellent strength and rigidity can be obtained. The upper limit is preferably 100% by mass, as this allows for a spunbond nonwoven fabric with excellent strength and rigidity.

[0017] Furthermore, thermoplastic resin A may contain, as necessary, commonly used additives such as antioxidants, weather stabilizers, light stabilizers, heat stabilizers, antistatic agents, antistatic additives, anti-fogging agents, anti-blocking agents, matting agents, antifungal agents, antibacterial agents, antiviral agents, flame retardants, metal oxides, hydrophilic agents, nucleating agents, pigments, lubricants including polyethylene wax, aliphatic bisamides and / or aliphatic monoamides, or other polymers, provided that the effects of the present invention are not impaired.

[0018] The melting point of thermoplastic resin A is preferably 200°C or higher and 320°C or lower. A spunbond nonwoven fabric with excellent heat resistance can be obtained when the melting point of thermoplastic resin A is preferably 200°C or higher, more preferably 220°C or higher, and even more preferably 240°C or higher. On the other hand, when the melting point of thermoplastic resin A is preferably 320°C or lower, more preferably 300°C or lower, and even more preferably 280°C or lower, it is possible to suppress the thermal degradation of the spunbond nonwoven fabric by thermoplastic resin B, which has a lower melting point than thermoplastic resin A (described later), and a spunbond nonwoven fabric with excellent quality can be obtained. In addition, the yarn discharged from the spinneret becomes easier to cool, excessive fusion between fibers is suppressed, and a spunbond nonwoven fabric with excellent uniformity of form can be obtained.

[0019] Here, the melting point of thermoplastic resin A refers to the maximum melting peak temperature obtained by measuring thermoplastic resin A using differential scanning calorimetry (DSC). When measuring the melting point of thermoplastic resin A from spunbond nonwoven fabric or the fibers constituting it, the value calculated by the following procedure shall be adopted. (1) Randomly take one small piece from the spunbond nonwoven fabric weighing between 0.5 mg and 5 mg. If measuring from the fibers, cut the fibers to obtain small pieces weighing between 0.5 mg and 5 mg. (2) For the small pieces from (1), differential scanning calorimeters (DSC, e.g., PerKin-Elmer's "DSC 8500", TA Instruments' "Q2000", etc.) are used to perform differential scanning calorimeter measurements twice under conditions ranging from room temperature to 350°C, with heating and cooling rates of 20°C / min, to obtain DSC curves. (3) Read the peak top temperature (melting peak temperature) of the melting endothermic peak from the second DSC curve, and set the highest melting peak temperature as the melting point of thermoplastic resin A.

[0020] Furthermore, since the small piece being measured also contains thermoplastic resin B, it is possible to measure this simultaneously. If there is concern that the thermoplastic resin B being measured will deteriorate due to heating up to the upper limit of the temperature range described in (2) above, it is also possible to lower the upper limit of the temperature range to about 280°C, as long as the melting endothermic peaks of thermoplastic resins A and B can be obtained.

[0021] Furthermore, when measuring from the raw material polymer, thermoplastic resin A, take a sample of 0.5 mg to 5 mg, perform the procedure in (2), read the peak top temperature (melting peak temperature) of the melting endothermic peak from the DSC curve during the second heating, and set the obtained melting peak temperature as the melting point of thermoplastic resin A.

[0022] The intrinsic viscosity (IV) of thermoplastic resin A is preferably 0.55 or more and 0.75 or less. When the intrinsic viscosity (IV) is preferably 0.55 or more, more preferably 0.60 or less, and even more preferably 0.62 or more, the single filament strength is increased. On the other hand, when the intrinsic viscosity (IV) is preferably 0.75 or less, more preferably 0.70 or less, and even more preferably 0.68 or less, the spindle properties when manufacturing the spunbond nonwoven fabric can be improved, and a spunbond nonwoven fabric of superior quality can be obtained.

[0023] In this invention, the intrinsic viscosity (IV) of thermoplastic resin A shall be the value obtained by the following method. (1) Dissolve 8 g of the sample in 100 mL of orthochlorophenol, and measure the relative viscosity η at a temperature of 25°C using an Ostwald viscometer according to the following formula. r To seek η r =η / η0=(t×d) / (t0×d0) ···(Formula). Here, η is the viscosity of the polymer solution, η0 is the viscosity of orthochlorophenol, t is the fall time of the solution (seconds), and d is the density of the solution (g / cm³). 3 ), t0 is the fall time of orthochlorophenol (seconds), and d0 is the density of orthochlorophenol (g / cm³). 3 ) represents. (2) Relative viscosity η r Therefore, calculate the intrinsic viscosity (IV) using the following formula and round it to the third decimal place. Intrinsic viscosity (IV)=0.0242ηr+0.2634 (formula).

[0024] [Thermoplastic resin B] The fibers constituting the spunbond nonwoven fabric of the present invention further include a thermoplastic resin B, which mainly consists of a polyolefin resin, as a constituent component.

[0025] The melting point of thermoplastic resin B is lower than that of thermoplastic resin A, and the melting point of thermoplastic resin B is (T m,B )℃ and the melting point (T) of thermoplastic resin A m,A The difference from )℃ is preferably 50℃ or more and 250℃ or less. (T m,B )℃ is (T m,A By having a melting point 50°C or more, preferably 70°C or more, and more preferably 80°C or more lower than (T), adhesion to the heat embossing roll and the like in the manufacturing process described later is suppressed, resulting in a spunbond nonwoven fabric with excellent strength. m,B )℃ is (T m,A By setting the spinning temperature to 250°C or lower, more preferably 200°C or lower, and even more preferably 180°C or lower, polymer degradation during spinning is suppressed, resulting in a spunbond nonwoven fabric with excellent productivity and quality.

[0026] Here, the melting point of thermoplastic resin B refers to the maximum melting peak temperature obtained by measuring thermoplastic resin B using differential scanning calorimetry (DSC). When measuring the melting point of thermoplastic resin B from spunbond nonwoven fabric, the value calculated by the following procedure shall be adopted. (1) Randomly select one small piece from the spunbond nonwoven fabric, weighing between 0.5 mg and 5 mg. (2) For the small pieces from (1), differential scanning calorimeters (DSC, e.g., PerKin-Elmer's "DSC 8500", TA Instruments' "Q2000", etc.) are used to perform differential scanning calorimeter measurements twice under nitrogen conditions, with heating and cooling rates of 20°C / min, from room temperature to 350°C, to obtain DSC curves. (3) Read the peak top temperature (melting peak temperature) of the melting endothermic peak from the second DSC curve, and set the lowest melting peak temperature as the melting point of thermoplastic resin B.

[0027] Furthermore, if there are concerns about the degradation of the thermoplastic resin B being measured by raising the temperature to the upper limit of the temperature range described in (2) above, it is also possible to lower the upper limit of the temperature range to approximately 280°C, as long as the melting endothermic peak of thermoplastic resin B can be measured.

[0028] Furthermore, when measuring from the raw material polymer, thermoplastic resin B, take a sample of 0.5 mg to 5 mg, perform the procedure in (2), read the peak top temperature (melting peak temperature) of the melting endothermic peak from the DSC curve during the second heating, and define the obtained melting peak temperature as the melting point of thermoplastic resin B.

[0029] Furthermore, the melting point of thermoplastic resin B is preferably 100°C or higher and 240°C or lower. A melting point of thermoplastic resin B of preferably 100°C or higher, more preferably 110°C or higher, and even more preferably 120°C or higher results in a spunbond nonwoven fabric with heat resistance suitable for practical use. On the other hand, a melting point of polyolefin resin P2 of preferably 240°C or lower, more preferably 210°C or lower, and even more preferably 180°C or lower prevents the sheet from sticking to the heating roll during heat bonding, preventing distortion and wrinkles from occurring in the sheet and reducing its quality, while also improving heat adhesion and resulting in a spunbond nonwoven fabric with excellent strength and rigidity.

[0030] Examples of thermoplastic resin B include polyethylene resins, polypropylene resins, polybutene resins, and polymethylpentene resins. Polyolefin resins are suitable for applications requiring heat adhesion, and among them, polyethylene resins and polypropylene resins are preferred due to their excellent spinnability. Furthermore, polyethylene resins are more preferably used because they can be heat-bonded at lower temperatures.

[0031] Polyethylene resins refer to resins having ethylene units as repeating units, and include ethylene homopolymers or copolymers of ethylene and various α-olefins. Among these, ethylene homopolymers are preferred to prevent a decrease in spinning stability and strength. As copolymers of ethylene and various α-olefins, copolymers of ethylene and α-olefins having 3 to 5 carbon atoms are preferred. Examples of α-olefins having 3 to 5 carbon atoms include propylene, 1-butene, and 1-pentene, with 1-butene being more preferred. By doing so, entanglement of molecular chains during melting is suppressed, preventing yarn breakage, and the increase in amorphous components prevents the sheet from sticking to the heating roll during heat bonding, thus preventing distortion and wrinkles from occurring in the sheet and reducing the quality of the spunbond nonwoven fabric.

[0032] When using copolymers of ethylene and various α-olefins, the copolymerization ratio of the α-olefin is preferably 0.1 mol% to 10 mol% relative to the polymerization component of the polyethylene resin. A copolymerization ratio of α-olefin of preferably 0.1 mol% to 10 mol%, more preferably 0.1 mol% to 7 mol%, and even more preferably 0.1 mol% to 5 mol%, suppresses yarn breakage during spinning and adhesion to heat embossing rolls during the manufacturing process described later, resulting in a spunbond nonwoven fabric with fewer defects such as distortion and wrinkles.

[0033] The α-olefin species and α-olefin copolymerization ratio in the polymerization components of polyethylene resins can be calculated, for example, from the detected peak positions and peak area ratios obtained by nuclear magnetic resonance (NMR) spectroscopy.

[0034] Examples of polyethylene resins include medium-density polyethylene, high-density polyethylene (hereinafter sometimes abbreviated as HDPE), or linear low-density polyethylene (hereinafter sometimes abbreviated as LLDPE). Among these, HDPE or LLDPE are preferred because they suppress yarn breakage during spinning in the manufacturing process described later, resulting in a spunbond nonwoven fabric with fewer surface defects.

[0035] The melting point of the polyethylene resin is preferably 100°C or higher and 150°C or lower. A melting point of 100°C or higher, more preferably 110°C or higher, and even more preferably 120°C or higher makes it easier to obtain heat resistance that is suitable for practical use. Furthermore, a melting point of 150°C or lower, more preferably 140°C or lower, and even more preferably 135°C or lower makes it easier to cool the yarn extruded from the spinneret in the manufacturing process described later, suppressing the fusion of fibers, resulting in a spunbond nonwoven fabric with excellent uniformity of texture.

[0036] The solid density of polyethylene resin is 0.935 g / cm³. 3 More than 0.970g / cm 3 Preferably, the following conditions apply: The solid density of the polyethylene resin is preferably 0.935 g / cm³. 3 More preferably 0.940 g / cm³ 3 More preferably 0.945 g / cm³ 3 As a result of the above, adhesion to heat embossing rolls and other components in the manufacturing process described later is suppressed, resulting in a spunbond nonwoven fabric with fewer defects such as distortion and wrinkles. Furthermore, the solid density of the polyethylene resin is preferably 0.970 g / cm³. 3 More preferably, 0.965 g / cm³ 3 More preferably, 0.960 g / cm³ 3 As a result of the following, yarn breakage during spinning in the manufacturing process described later is suppressed, resulting in a spunbond nonwoven fabric with fewer surface defects.

[0037] In this invention, the solid density (g / cm³) of the polyethylene resin is specified. 3 The value to be used shall be the value calculated by the following procedure. (1) Soak the polyethylene resin in ethanol to wash it, and then dry it in the open air. (2) The density of the dried resin is determined by the buoyancy method using a water-ethanol mixture. (3) Perform the same measurement five times using different resin pieces and obtain the measured density value (g / cm³). 3 ) are averaged and rounded to the fourth decimal place to obtain the solid density of polyethylene resin (g / cm³). 3 )

[0038] On the other hand, examples of polypropylene resins include propylene homopolymers or copolymers of propylene with one or more olefins selected from ethylene and / or various α-olefins other than propylene (hereinafter collectively referred to as "α-olefins, etc."). Among these, propylene homopolymers are preferred in order to prevent a decrease in spinning stability and strength.

[0039] When using a copolymer of propylene and α-olefins, etc., ethylene and 1-butene are preferred as copolymer components due to their excellent spinning stability, with ethylene being more preferred. Furthermore, the copolymerization ratio is preferably 15 mol% or less, more preferably 10 mol% or less, and even more preferably 5 mol% or less, in order to prevent a decrease in spinning stability and strength.

[0040] The types of α-olefins and other compounds in the polymerization components of polypropylene resins, as well as the copolymerization ratio of α-olefins and other compounds, can be calculated, for example, from the detected peak positions and peak area ratios obtained by nuclear magnetic resonance (NMR) spectroscopy.

[0041] The melting point of the polypropylene resin is preferably 120°C or higher and 180°C or lower. A melting point of 120°C or higher, more preferably 130°C or higher, and even more preferably 140°C or higher makes it easier to obtain heat resistance that is suitable for practical use. Furthermore, a melting point of 180°C or lower, more preferably 170°C or lower, and even more preferably 160°C or lower makes it easier to cool the yarn extruded from the spinneret, suppressing fusion between fibers and resulting in a spunbond nonwoven fabric with excellent uniformity of texture.

[0042] Furthermore, the thermoplastic resin B may, as necessary, contain additives such as commonly used antioxidants, weather stabilizers, light stabilizers, heat stabilizers, antistatic agents, antistatic additives, fogging agents, antiblocking agents, matting agents, antibacterial agents, antifungal agents, antiallergens, antiviral agents, vitamins, flame retardants, metal oxides, hydrophilic agents, nucleating agents, pigments, lubricants including polyethylene wax, aliphatic bisamides and / or aliphatic monoamides, or other polymers, within the limits that do not impair the effects of the present invention.

[0043] The melt flow rate (hereinafter sometimes abbreviated as MFR) of thermoplastic resin B is preferably 1 g / 10 min or more and 100 g / 10 min or less. When the MFR of thermoplastic resin B is preferably 1 g / 10 min or more, more preferably 10 g / 10 min or more, and even more preferably 20 g / 10 min or more, yarn breakage during spinning in the manufacturing process described later is suppressed, resulting in a spunbond nonwoven fabric with fewer surface defects. On the other hand, when the MFR of thermoplastic resin B is preferably 100 g / 10 min or less, more preferably 80 g / 10 min or less, and even more preferably 60 g / 10 min or less, the single yarn strength is increased, resulting in a spunbond nonwoven fabric with excellent strength and rigidity. Of course, the MFR of the polyolefin resin used in the present invention can also be adjusted by blending two or more resins with different MFRs in any proportion.

[0044] The MFR of this thermoplastic resin B will be the value measured by ASTM D1238-10 "Standard Test Method for Melt Flow Rates of Thermoplastics by Extrusion Plastometer" (Method A). According to this standard, polyethylene is measured at a load of 2.16 kg and a temperature of 190°C, and polypropylene is measured at a load of 2.16 kg and a temperature of 230°C.

[0045] Furthermore, while resins containing petroleum-derived components or biomass-derived components can be used as polyolefin resins, resins containing biomass-derived components are preferred. It is also preferable that the biomass-derived carbon accounts for 20% or more of the total carbon content of the polyolefin resin, more preferably 50% or more, and even more preferably 90% or more. This results in a spunbond nonwoven fabric with a low environmental impact.

[0046] Furthermore, the polyolefin resin of the present invention includes not only newly obtained polyolefin resins obtained by polymerizing biomass-derived components, but also recycled polyolefin resins that contain biomass-derived polyolefin resins.

[0047] The proportion of carbon atoms derived from biomass is measured by the carbon-14 concentration measurement method using accelerator mass spectrometry (Method B) described in ASTM D6866-22, "Standard Test Methods for Determining the Biobased Content of Solid, Liquid, and Gaseous Samples Using Radiocarbon Analysis." This method allows us to determine whether a component is derived from biomass or petroleum based on the amount of radioactive isotopes of the carbon atoms. If all carbon atoms are derived from biomass, the proportion of biomass-derived carbon atoms will be 100%.

[0048] [fiber] The spunbond nonwoven fabric of the present invention is composed of core-sheath type composite fibers, wherein the core component of the core-sheath type composite fiber is a thermoplastic resin A mainly composed of polyester resin, and the sheath component of the core-sheath type composite fiber is a thermoplastic resin B mainly composed of polyolefin resin.

[0049] By doing so, a composite fiber is created that combines single-fiber strength and heat-bonding properties, resulting in a spunbond nonwoven fabric with sufficient strength and rigidity for practical use.

[0050] As the composite form of the core-sheath type composite fiber constituting the spunbond nonwoven fabric of the present invention, for example, composite forms such as concentric core-sheath type and eccentric core-sheath type can be used. Among these, a concentric core-sheath type composite form is more preferable because it has excellent spinnability and allows the fibers to be uniformly bonded to each other by heat bonding.

[0051] The cross-sectional shape of the composite fibers constituting the spunbond nonwoven fabric of the present invention may be a round cross-section, a flat cross-section, or an irregular cross-section such as a Y-shape or a C-shape. Among these, a round cross-section is more preferable because it offers excellent spinnability and, by spinning at a high spinning speed, can produce composite fibers with excellent single-fiber strength.

[0052] Furthermore, the composite fibers constituting the spunbond nonwoven fabric of the present invention preferably have an average single fiber diameter of 8.0 μm or more and 30.0 μm or less. Within this range of average single fiber diameter, if the lower limit is preferably 9.0 μm or more, more preferably 9.0 μm or more, and even more preferably 10.0 μm or more, a spunbond nonwoven fabric with excellent breathability is obtained. On the other hand, within the above range, if the upper limit is preferably 30.0 μm or less, more preferably 25.0 μm or less, even more preferably 20.0 μm or less, and particularly preferably 18.0 μm or less, the spunbond nonwoven fabric has a good weave and a spunbond nonwoven fabric with small variations in strength and rigidity.

[0053] Furthermore, the average single fiber diameter (μm) of the composite fibers constituting the spunbond nonwoven fabric shall be the value calculated by the following procedure. (1) Take 10 small sample pieces (100 x 100 mm) randomly from the spunbond nonwoven fabric. (2) Take surface photographs at magnifications of 300x to 1000x using a microscope (e.g., Keyence Corporation's "VW-9000") or a scanning electron microscope (e.g., Keyence Corporation's "VHX-D500"), and measure the width (diameter) of 50 non-fused composite fibers from each sample. If the cross-section of the composite fiber is irregular, create a measurement sample in which the cross-section can be observed and observe it to measure the cross-sectional area and determine the diameter of a perfect circle with the same cross-sectional area. A non-fused portion is a part in which the fibers are not fused to each other or deformed. (3) Average the diameter values ​​of the 50 measured fibers and round to the second decimal place to obtain the average single fiber diameter (μm).

[0054] Furthermore, this average single fiber diameter can be controlled by appropriately adjusting the area ratio of the core components in the fiber cross-section of thermoplastic resin A and thermoplastic resin B of the composite fiber, and / or the spinning temperature, the amount of extrusion per single hole of the spinneret, the spinning speed, etc., as described later.

[0055] The core-sheath type composite fiber according to the present invention has an area ratio (P) of the core component in the fiber cross-section of one surface portion. C1 ) satisfies the following equation 1 0.10≦P C1 ≦0.70 (Equation 1).

[0056] P C1 Preferably, P is 0.10 or higher, more preferably 0.30 or higher, and even more preferably 0.50 or higher, which improves the single-fiber strength, resulting in a spunbond nonwoven fabric with sufficient strength for practical use, and also suppresses adhesion to heat embossing rolls and the like in the manufacturing process described later, resulting in a spunbond nonwoven fabric with fewer surface defects such as wrinkles and unevenness. On the other hand, P C1When the ratio is 0.70 or less, preferably 0.65 or less, the sheath components fuse firmly together during heat bonding, resulting in a spunbond nonwoven fabric with sufficient strength and rigidity for practical use.

[0057] Furthermore, the area ratio P of the core component in the cross-section of the core-sheath type composite fiber in one surface portion of the spunbond nonwoven fabric. C1 The value to be used shall be the value calculated by the following procedure. (1) Take 10 small samples randomly from the spunbond nonwoven fabric. (2) The spunbond nonwoven fabric sample is embedded in bisphenol epoxy resin. (3) After the resin has hardened, sections are cut out using a freeze microtome so that the cut surface is near the center of the unfused portion of the spunbond nonwoven fabric. At this time, the cross-sectional sample is cut so that it passes through the center of the unfused portion of the spunbond nonwoven fabric. (4) For each small sample piece, take a cross-sectional photograph using a microscope (e.g., Keyence Corporation's "VW-9000") or a scanning electron microscope (e.g., Keyence Corporation's "VHX-D500"). At this time, take the photograph so that the entire thickness of the spunbond nonwoven fabric is captured. (5) In the cross-sectional photograph, in the thickness direction of the spunbond nonwoven fabric, within a range of 20% from one surface side, the cross-sectional area S of the core component composed of thermoplastic resin A is measured for all measurable composite fiber cross-sections. A1,F and the cross-sectional area S of the sheath component composed of thermoplastic resin B B1,F The cross-sectional area shall be measured. If the interface between different thermoplastic resins in the composite fiber is unclear in the aforementioned cross-sectional photograph, each fiber shall be photographed at a magnification (approximately 300x to 3000x) that allows the interface between the different thermoplastic resins to be clearly observed, and the cross-sectional area shall be measured. (6) Area ratio P of the core component of each fiber in one of the surface portions C1,F The following formula is used to calculate it. P C1,F =S A1,F / (S A1,F +S B1,F )...(expression). (7) Calculated P C1,F The average value of P C1 They will be hired as such.

[0058] Furthermore, the area ratio P of the core component in the other surface portion. C2 The same method can be used to calculate the cross-sectional area S in the thickness direction of the spunbond nonwoven fabric within the cross-sectional photograph. A1 For all measurable cross-sections of composite fibers, within a 20% range from the opposite side of the surface to which the measurement was taken, the cross-sectional area S of the core component composed of thermoplastic resin A was measured. A2 and the cross-sectional area S of the sheath component composed of thermoplastic resin B B2 Measure the volume-area ratio P of the core component in the other surface portion. C2 The following formula is used to calculate it. P C2 =S A2 / (S A2 +S B2 )...(expression).

[0059] In the present invention, the core-sheath type composite fiber has an area ratio (P) of the core component in the other surface portion. C2 ) is the area ratio of the core component in the part on one surface side (P C1 For ) the following equation 2 is satisfied 0.10≦P C2 -P C1 ≦0.55 (Equation 2).

[0060] P C2 -P C1 When P is 0.10 or higher, preferably 0.15 or higher, and more preferably 0.20 or higher, adhesion to the heat embossing roll during the heat sealing process is suppressed, resulting in a spunbond nonwoven fabric with excellent heat sealing processability. On the other hand, P C2 -P C1 When the ratio is 0.55 or less, preferably 0.45 or less, and more preferably 0.40 or less, the sheath components fuse together firmly during heat bonding, resulting in a spunbond nonwoven fabric with sufficient strength and rigidity for practical use.

[0061] [Spunbond nonwoven fabric] The spunbond nonwoven fabric of the present invention is composed of the aforementioned core-sheath type composite fibers.

[0062] The spunbond nonwoven fabric of the present invention exhibits a single melting peak originating from the polyolefin resin when differential scanning calorimetry is performed. In other words, it is preferable to use one type of polyolefin resin as the thermoplastic resin B constituting the sheath component of the core-sheath composite fiber constituting the spunbond nonwoven fabric of the present invention. By doing so, the fiber web can be bonded at an appropriate temperature, interlayer delamination of the spunbond nonwoven fabric is less likely to occur, and a spunbond nonwoven fabric with excellent strength can be obtained.

[0063] Melting peaks originating from polyolefin resins can be identified, for example, by combining the results of differential scanning calorimetry with the detection peak positions obtained by nuclear magnetic resonance (NMR) and the spectral results of Fourier transform infrared spectrophotometer (FTIR).

[0064] In the spunbond nonwoven fabric of the present invention, it is preferable that the difference between the temperature of the melting peak with the largest heat of fusion and the temperature of the melting peak with the second largest heat of fusion, as detected when differential scanning calorimetry is performed on the spunbond nonwoven fabric, is between 50°C and 250°C. When the difference between the temperature of the melting peak with the largest heat of fusion and the temperature of the melting peak with the second largest heat of fusion is preferably 50°C or more, more preferably 70°C or more, and even more preferably 90°C or more, during bonding, only the low-melting-point components are heat-fused while the high-melting-point components maintain their strength, resulting in a spunbond nonwoven fabric with excellent strength. On the other hand, when the difference between the temperature of the melting peak with the largest heat of fusion and the temperature of the melting peak with the second largest heat of fusion is preferably 250°C or less, more preferably 200°C or less, and even more preferably 180°C or less, degradation of the polymer during spinning is prevented, resulting in a spunbond nonwoven fabric with better productivity and quality.

[0065] In the present invention, when the main component of thermoplastic resin A is polyethylene terephthalate resin and the main component of thermoplastic resin B is polyethylene resin, if the difference between the melting peak temperature with the largest heat of fusion and the melting peak temperature with the second largest heat of fusion is 50°C or more and 250°C or less, the core-sheath composite fibers can adhere to other core-sheath composite fibers while maintaining the strength of the core component, resulting in a spunbond nonwoven fabric with excellent strength.

[0066] The melting point and heat of fusion of each resin can be measured using a differential scanning calorimeter in the following manner. (1) Take a sample of approximately 2 mg from the spunbond nonwoven fabric, excluding 10 cm from the edge in the width direction. (2) Using a differential scanning calorimeter (DSC, e.g., PerKin-Elmer's "DSC 8500", TA Instruments' "Q2000", etc.), perform two differential scanning calorimeter measurements under nitrogen conditions, with heating and cooling rates of 20°C / min, from room temperature to 350°C, and perform three differential scanning calorimeter measurements to obtain the second DSC curve. (3) The arithmetic mean of the temperatures of the endothermic peaks obtained from the three measurements is taken as the melting point, and the arithmetic mean of the amount of heat absorbed, calculated from the area of ​​the endothermic peak, is taken as the heat of fusion.

[0067] Furthermore, if there are concerns about the degradation of the thermoplastic resin B being measured by raising the temperature to the upper limit of the temperature range described in (2) above, it is also possible to lower the upper limit of the temperature range to about 280°C, as long as the melting endothermic peak of thermoplastic resin A can be obtained.

[0068] The basis weight of the spunbond nonwoven fabric of the present invention is 10 g / m². 2 More than 100g / m 2 The following is preferable: The basis weight is preferably 10 g / m². 2 Above, a comfortable 15g / m 2 More preferably 20 g / m² 2By doing so, a spunbond nonwoven fabric with mechanical strength suitable for practical use can be obtained. On the other hand, the basis weight is preferably 100 g / m². 2 More preferably 90g / m 2 More preferably 80 g / m 2 By doing the following, a spunbond nonwoven fabric with excellent processability and breathability for packaging materials can be produced.

[0069] In the present invention, the basis weight of the spunbond nonwoven fabric is measured according to the following procedure, in accordance with "6.2 Mass per unit area" of JIS L1913:2010 "General Test Methods for Nonwoven Fabrics". (1) Take three 20cm x 25cm test pieces for every 1m of width of the sample. (2) Weigh the mass (g) of each under standard conditions. (3) The average value is 1m 2 Mass per unit (g / m³) 2 It is represented as ).

[0070] The apparent density of the aforementioned spunbond nonwoven fabric is 0.05 g / cm³. 3 More than 0.90g / cm 3 Preferably, the apparent density is 0.05 g / cm³. 3 More preferably 0.10 g / cm³ 3 More preferably 0.15 g / cm³ 3 As a result, the spunbond nonwoven fabric can be made that suppresses the occurrence of fuzzing and delamination, and that has sufficient tear strength and handling properties for use as a packaging material. On the other hand, the apparent density is preferably 0.90 g / cm³. 3 More preferably, 0.75 g / cm³ 3 More preferably, 0.55 g / cm³ 3 The following conditions prevent a reduction in the voids within the spunbond nonwoven fabric, thereby preventing the impairing of the spunbond nonwoven fabric's breathability. The apparent density can be controlled by appropriately adjusting the average single fiber diameter and / or the heat bonding conditions described later (shape of the bonding area, heat fusion rate, temperature, and linear pressure, etc.).

[0071] The apparent density of the spunbond nonwoven fabric (g / cm 3 ) is calculated by the following procedure. (1) The thickness (mm) of the spunbond nonwoven fabric is measured according to the following procedure, in conformity with 6.1.1 "Method A" of JIS L1913:2010 "General nonwoven fabric test methods". (A) Using a pressurizing indenter with a diameter of 10 mm, the thickness is measured at 10 points per meter at equal intervals in the width direction of the spunbond nonwoven fabric under a load of 10 kPa, in units of 0.01 mm. (B) The third decimal place of the average value of the above 10 points is rounded off. (2) From the basis weight and the thickness before the above rounding, the apparent density is calculated based on the following formula, and the third decimal place is rounded off Apparent density (g / cm 3 ) = [Basis weight (g / m 2 )] / [Thickness (mm)] × 10 -3 ···(Formula).

[0072] The product of tensile strength and elongation per basis weight of the spunbond nonwoven fabric is preferably 1.0 (N / 50mm) / (g / m 2 ) or more and 4.0 (N / 50mm) / (g / m 2 ) or less. The product of tensile strength and elongation per basis weight is preferably 1.0 (N / 50mm) / (g / m 2 ) or more, more preferably 1.2 (N / 50mm) / (g / m 2 ) or more, and even more preferably 1.4 (N / 50mm) / (g / m 2 ) or more, whereby a spunbond nonwoven fabric having excellent strength even at a low basis weight can be obtained. On the other hand, the product of tensile strength and elongation per basis weight is preferably 4.0 (N / 50mm) / (g / m 2 ) or less, more preferably 3.5 (N / 50mm) / (g / m 2 ) or less, and even more preferably 3.0 (N / 50mm) / (g / m 2 ) or less, which can prevent the flexibility of the spunbond nonwoven fabric from decreasing or the hand feel from being impaired.

[0073] The tensile strength-to-elongation product per basis weight of the spunbond nonwoven fabric can be controlled by appropriately adjusting the MFR of the thermoplastic resins A and B, additives, the average single fiber diameter of the core-sheath type composite fibers, the spinning rate (described later), preheating conditions (temperature, linear pressure, etc.), and heat bonding conditions (shape of the bonded area, heat fusion rate, temperature, and linear pressure, etc.).

[0074] In the present invention, the tensile strength-to-elongation product per basis weight of the spunbond nonwoven fabric shall be the value obtained by the following procedure, in accordance with "6.3 Tensile strength and elongation (ISO method)" of JIS L1913:2010 "General nonwoven fabric testing methods". (1) Take three 50mm x 300mm test pieces for every 1m of spunbond nonwoven fabric width, with the longer side facing the longitudinal direction of the spunbond nonwoven fabric. (2) Grasp the test specimens and set them in the tensile testing machine at intervals of 200 mm. (3) A tensile test is conducted at a tensile speed of 100 mm / min, and the maximum strength and elongation at maximum strength are measured. Here, the elongation is expressed as the ratio of the elongation to the initial gripping distance, not as a percentage (%). (4) Determine the average of the maximum strength and elongation at maximum strength measured for each test specimen, calculate the tensile strength-to-elongation product per unit weight based on the following formula, and round to two decimal places. Tensile strength product per unit area ((N / 50mm) / (g / m) 2 )) = [Average value of maximum strength (N / 50mm)] × [Average value of elongation at maximum strength (-)] / Basis weight (g / m 2 )...(expression).

[0075] The longitudinal direction of the spunbond nonwoven fabric in this invention is determined by the following method. If the longitudinal direction can be determined from the appearance of the spunbond nonwoven fabric, that is, if the winding direction on the nonwoven fabric roll can be uniquely determined, this direction shall be considered the longitudinal direction. On the other hand, if the longitudinal direction cannot be determined from the appearance, such as when the spunbond nonwoven fabric is cut or not in a roll, the longitudinal direction shall be determined by the following procedure. (1) Within the plane of the spunbond nonwoven fabric, one arbitrary direction is determined, and a test piece measuring 300 mm in length and 50 mm in width is taken along that direction. (2) Similarly, test specimens measuring 30 mm in length and 50 mm in width are taken in directions rotated 30, 60, and 90 degrees from the direction in which the specimen was taken. (3) For each test specimen in each direction, the maximum strength of each specimen is measured based on the above-mentioned method for measuring the tensile strength product per basis weight of the spunbond nonwoven fabric (2) to (3), the average value of the three points is calculated, and the value rounded to the first decimal place is taken as the tensile strength of the spunbond nonwoven fabric in each direction. (4) The direction in which the measured value is highest shall be considered the longitudinal direction of the spunbond nonwoven fabric. If there are two or more directions with the highest value, the direction in which the tensile strength in the direction perpendicular to those directions is lower shall be considered the longitudinal direction of the spunbond nonwoven fabric. If there are two or more directions with the highest value, and the tensile strength in the direction perpendicular to those directions is also equal, for example, if the tensile strength in all four directions is equal, then one of those four directions shall be considered the longitudinal direction.

[0076] The spunbond nonwoven fabric of the present invention preferably has heat-fused portions. Heat-fused portions refer to areas where the fibers are melted and fused together to such an extent that the cross-sectional shape of the fibers differs from the shape of other parts, such as by being fused in the cross-sectional direction of the spunbond nonwoven fabric, and furthermore, the fibers melt to such an extent that the area becomes a lump or a film. Specifically, these are portions that are heat-fused by a heat embossing roll or portions that are heat-fused by ultrasonic vibration. Having heat-fused portions results in a spunbond nonwoven fabric with excellent strength and rigidity. The heat-fused rate of the spunbond nonwoven fabric of the present invention is preferably 3% or more and 60% or less. By setting the heat-fused rate to preferably 3% or more, more preferably 5% or more, and even more preferably 10% or more, sufficient strength can be imparted to the spunbond nonwoven fabric, and the occurrence of fuzzing on the surface can be suppressed. Furthermore, by preferably setting the heat fusion rate to 60% or less, more preferably to 45% or less, and even more preferably to 30% or less, a spunbond nonwoven fabric with appropriate mechanical strength and flexibility suitable for packaging materials can be obtained.

[0077] The thermal bonding rate in this invention can be calculated by the following method. (1) Take 10 small sample pieces randomly from the spunbond nonwoven fabric. (2) Using a scanning electron microscope, take a total of 10 images, one from each sample, at a magnification (approximately 20x to 50x) that includes the repeating units of the fused area in each image. (3) From each photograph, the area of ​​each fused part and the area of ​​the smallest unit of the repeating embossing pattern including the fused and non-fused parts were determined, and these were averaged. Then, the thermal fusion rate was calculated using the following formula and rounded to the first decimal place. Thermal fusion rate (%) = [(Area per fused part) × (Number of fused parts in the smallest unit of the repeating pattern) / (Area of ​​the smallest unit of the repeating pattern)] × 100 ... (formula). However, if the repeating pattern includes multiple fused parts of different sizes, the following formula shall be used to determine the size. [(Total area of ​​fused parts included in the smallest unit of the repeating pattern) / (Area of ​​the smallest unit of the repeating pattern)] × 100 ... (Formula).

[0078] [Method for manufacturing spunbond nonwoven fabric] Next, preferred embodiments of the method for producing the spunbond nonwoven fabric of the present invention will be described in detail. The spunbond nonwoven fabric of the present invention is a long-fiber nonwoven fabric produced by the spunbond method. The spunbond method is excellent in terms of productivity and mechanical strength, and can suppress fluffing and fiber shedding that are common in short-fiber nonwoven fabrics. Furthermore, laminating multiple layers of collected spunbond nonwoven fiber webs or heat-fused spunbond nonwoven fabrics (both denoted as S) in layers such as SS, SSS, and SSSS is also a preferred embodiment because it improves productivity and uniformity of the fabric.

[0079] The present invention provides a method for producing spunbond nonwoven fabric, The process includes the steps of: forming a first fiber web composed of a first core-sheath type composite fiber, the core component of which is a thermoplastic resin A mainly composed of polyester resin, and the sheath component of which is a thermoplastic resin B mainly composed of polyolefin resin; forming a second fiber web on the first fiber web, the second fiber web composed of a second core-sheath type composite fiber, the core component of which is a thermoplastic resin A mainly composed of polyester resin, and the sheath component of which is a thermoplastic resin B mainly composed of polyolefin resin, to form a laminated web; and heat-sealing the laminated web with a pair of heat rolls.

[0080] In the spunbond method, molten thermoplastic resin is first spun out as long fibers from a spinneret, which are then cooled and stretched, and finally collected on a moving net to form the material. Stretching may also be performed by suction using compressed air via an ejector or similar device.

[0081] The shape of the spinneret and ejector is not particularly limited, but various shapes such as round or rectangular can be used. Among these, a combination of a rectangular spinneret and a rectangular ejector is preferred because it uses relatively little compressed air, is energy-efficient, is less prone to fusing or friction between yarns, and facilitates yarn opening.

[0082] In this invention, thermoplastic resin A and thermoplastic resin B are melted in separate extruders, weighed, and supplied to a single spinneret to be spun out as a composite fiber.

[0083] The spinning temperature when spinning composite fibers is preferably 200°C to 320°C, more preferably 240°C to 300°C, and even more preferably 270°C to 290°C. By setting the spinning temperature within the above range, energy consumption during manufacturing is reduced, and thermal degradation of thermoplastic resin A and thermoplastic resin B is suppressed, resulting in a stable molten state and excellent spinnability.

[0084] The spun filament yarn is then cooled. Methods for cooling the spun yarn include, for example, forcibly blowing cold air onto the yarn, allowing it to cool naturally with the ambient temperature around the yarn, and adjusting the distance between the spinneret and the ejector, or a combination of these methods can be employed. The cooling conditions can be appropriately adjusted considering the discharge rate per single hole of the spinneret, the spinning temperature, and the ambient temperature.

[0085] Next, the cooled and solidified filament is stretched and pulled by compressed air injected from an ejector.

[0086] The spinning speed is preferably 3000 m / min to 6500 m / min, more preferably 3500 m / min to 6000 m / min, and even more preferably 4000 m / min to 6500 m / min. By setting the spinning speed to 3000 m / min to 6500 m / min, not only is high productivity achieved, but the orientation and crystallization of the fibers can be promoted, thereby enabling the production of high-strength long fibers. The spinning speed can be controlled by appropriately adjusting the spinning temperature, the amount of extrusion per single hole of the spinneret, the distance between the spinneret and the ejector, and the conditions for cooling the spun yarn (temperature and airflow of cold air, etc.).

[0087] Next, the obtained long fibers are collected on a moving net to obtain a first fiber web. Here, the first fiber web has a core component of thermoplastic resin A, which is mainly composed of polyester resin, and a sheath component of thermoplastic resin B, which is mainly composed of polyolefin resin.

[0088] Next, the long fibers obtained by spinning in the above method are collected on the first fiber web to obtain a second fiber web. Here, the first fiber web has a core component that is a thermoplastic resin A mainly composed of polyester resin, and a sheath component that is a thermoplastic resin B mainly composed of polyolefin resin. In the present invention, the second fiber web may be formed directly on the first fiber web, or one or more other fiber webs may be formed on the first fiber web, and the second fiber web may be formed on top of them.

[0089] The spunbond nonwoven fabric obtained in this invention satisfies the following formulas 1 and 2. 0.10≦P C1 ≦0.70 (Formula 1) 0.10≦P C2 -P C1 ≦0.55 (Equation 2). Here, P C1 P is the area ratio (unitless) of the core component in the cross-section of the core-sheath type composite fiber in the portion of one surface side of the spunbond nonwoven fabric, C2 This is the area ratio (unitless) of the core component in the cross-section of the core-sheath type composite fiber in the other surface portion of the spunbond nonwoven fabric.

[0090] P C1 and P C2 This can be adjusted by changing the ratio of thermoplastic resin A to thermoplastic resin B when melting thermoplastic resin A and thermoplastic resin B in separate extruders, weighing them, and supplying them to a single spinneret to spin them out as a composite fiber. Specifically, the area ratio of the cores of the long fibers forming the first fiber web should be adjusted so that the area ratio of the core component in the core-sheath composite cross-section in the spunbond nonwoven fabric satisfies Equation 1, and the area ratio of the cores of the long fibers forming the second fiber web should be adjusted so that it satisfies Equation 2.

[0091] In the present invention, it is also preferable to temporarily bond the laminated fiber web to one side of it on the net by contacting it with a hot flat roll. This prevents the surface layer of the laminated fiber web from peeling or being blown away during transport on the net, which can worsen the fabrication, and improves the transportability from the collection of the yarn to the heat fusion.

[0092] Next, the obtained laminated fiber web is heat-fused. The method for heat-fusing the laminated fiber web is not particularly limited, but preferred methods include heat-fusion using various rolls, such as a heat-embossing roll in which a pair of upper and lower roll surfaces are each engraved (with raised and recessed areas), a heat-embossing roll consisting of a combination of a roll with one flat (smooth) surface and a roll with an engraved (raised and recessed area) surface, and heat-fusion using ultrasonic vibration of a horn.

[0093] In particular, it is preferable to use a heat embossing roll in which a pair of upper and lower roll surfaces are each engraved (with raised or recessed areas), or a heat embossing roll consisting of a combination of a roll with one flat (smooth) surface and a roll with an engraved (raised or recessed area) surface. By doing so, productivity can be improved, and a regular fused area can be formed, thereby improving the strength of the spunbond nonwoven fabric.

[0094] As for the surface material of the heat embossing rolls, it is preferable to use a pair of metal rolls in order to obtain a sufficient heat fusion effect and to prevent the engraving (recessed portion) of one embossing roll from being transferred to the surface of the other roll.

[0095] The shape of the fused portion, such as the heat embossing roll, can be selected according to the application in which the spunbond nonwoven fabric is used, and examples include circular, elliptical, square, rectangular, parallelogram, rhombus, regular hexagon, and regular octagon.

[0096] Furthermore, it is preferable that the heat-sealed portions of the spunbond nonwoven fabric are regularly spaced at regular intervals in both the longitudinal and transverse directions. To achieve this, it is preferable that the heat-sealed portions of the heat embossing roll be regularly arranged in the shape exemplified above. By doing so, variations in strength and anisotropy of the spunbond nonwoven fabric can be reduced.

[0097] The surface temperature of the thermal embossing roll in the heat fusion process is determined by the melting point T of the thermoplastic resin B being used. m,B (T m,B -30)℃ or higher (T m,B It is preferable that the surface temperature of the thermocalender roll be (T) or lower. m,B -30°C or higher, more preferably (T m,B By setting the temperature to -25°C or higher, a spunbond nonwoven fabric with sufficient strength for practical use can be obtained through appropriate fusion. m,B (T)℃ or lower, more preferably (T m,B (T)℃ or lower, more preferably (T m,B By keeping the temperature below +4°C, excessive fusion is suppressed, and the spunbond nonwoven fabric can be obtained with appropriate breathability and processability suitable for use as a packaging material.

[0098] The linear pressure of the heat embossing roll during heat bonding is preferably 50 N / cm or more and 500 N / cm or less. By setting the linear pressure of the roll preferably to 50 N / cm or more, more preferably to 100 N / cm or more, and even more preferably to 150 N / cm or more, strong heat bonding can be achieved, and a spunbond nonwoven fabric with strength suitable for practical use can be obtained. On the other hand, by setting the linear pressure of the heat embossing roll preferably to 500 N / cm or less, more preferably to 400 N / cm or less, and even more preferably to 300 N / cm or less, it is possible to suppress a decrease in tear strength due to excessive heat bonding.

[0099] Furthermore, in this invention, in order to adjust the thickness of the spunbond nonwoven fabric, heat compression can be applied using a thermal calender roll consisting of a pair of upper and lower flat rolls before and / or after heat bonding with the heat embossing roll described above. In this case, the definition of fused and unfused parts does not change as a result of this heat compression process. The linear pressure of the thermal calender roll during this heat compression process is preferably 10 N / cm or more and 100 N / cm or less. By setting the linear pressure of the roll to preferably 10 N / cm or more, more preferably 20 N / cm or more, and even more preferably 30 N / cm or more, uniform heat compression can be achieved, and a spunbond nonwoven fabric with uniform thickness can be obtained. On the other hand, by setting the linear pressure of the thermal calender roll to preferably 100 N / cm or less, more preferably 80 N / cm or less, and even more preferably 70 N / cm or less, it is possible to suppress a decrease in heat sealability due to excessive heat compression. In addition, the temperature of the thermal calender roll during the heat compression process is the melting point T of the thermoplastic resin B. m,B It is preferable that the temperature be at least 10°C lower than the specified temperature. This prevents a decrease in heat sealability due to excessive heat compression. The upper and lower flat rolls refer to metal rolls or elastic rolls with no irregularities on their surface, and can be used in pairs of metal rolls or metal rolls and elastic rolls.

[0100] Furthermore, an elastic roll, in this context, refers to a roll made of a material that has elasticity compared to a metal roll. Examples of elastic rolls include so-called paper rolls such as paper, cotton, and aramid paper, as well as resin rolls made of urethane resin, epoxy resin, silicone resin, polyester resin, hard rubber, and mixtures thereof.

[0101] Furthermore, the spunbond nonwoven fabric of the present invention may be post-processed to have functional agents such as antibacterial agents, antifungal agents, anti-allergen agents, antiviral agents, vitamins, and flame retardants attached to the fiber surface. In particular, when the spunbond nonwoven fabric of the present invention is used as a filter, the effect of imparting these functionalities can be significantly enhanced compared to conventional filters.

[0102] Methods for applying functional agents to the fiber surface include coating methods using gravure rolls, kiss rolls, impregnation methods, and spraying methods. Furthermore, because of their excellent safety and low environmental impact, the solvent used to dilute the functional agent is preferably water-based. Here, water-based solvents include water alone, or aqueous solutions containing water-soluble organic solvents such as lower alcohols like methanol and ethanol, lower ketones like acetone and methyl ethyl ketone, lower carboxylic acids like acetic acid, and glycols like ethylene glycol, propylene glycol, and diethylene glycol, which can be selected according to the purpose.

[0103] [Packaging material] The spunbond nonwoven fabric of the present invention has a ratio of the area of ​​the core component in the cross-section of the core-sheath type composite fiber in one surface portion thereof. C1 This P is defined as a specific range. C1 And the area ratio P of the core component in the cross-section of the core-sheath type composite fiber on the other surface side. C2By ensuring a specific relationship between these factors, the area ratio of the sheath component of the core-sheath composite fiber differs between one surface of the spunbond nonwoven fabric and the other surface. This results in good adhesive strength when one surface is used as the heat-sealing side, while suppressing fusion to the heat-sealing machine on the other surface, thus providing good processability. Furthermore, the relatively high area ratio of the core component on the other surface results in superior strength for the heat-sealed product. Additionally, differential scanning calorimetry of the spunbond nonwoven fabric shows a single melting peak originating from the polyolefin resin. This indicates that only one type of polyolefin resin is used for the sheath component of the core-sheath composite fiber, thus suppressing over-adhesion and resulting in a high-quality packaging material.

[0104] In other words, the spunbond nonwoven fabric of the present invention has good heat-sealing properties and can be easily bonded with other materials or processed into bags by heat bonding, making it suitable for packaging materials for desiccants, dehumidifiers, and wrapping. That is, the packaging material of the present invention includes the spunbond nonwoven fabric of the present invention. [Examples]

[0105] Next, the spunbond nonwoven fabric of the present invention will be described in detail based on the examples. However, the present invention is not limited to these examples.

[0106] [Measurement method] The evaluation methods and measurement conditions used in the examples are described below. Unless otherwise specified, the measurements of each physical property were performed based on the methods described above.

[0107] (1) Differential scanning calorimetry: A differential scanning calorimeter, the "Q2000" manufactured by TA Instruments, was used to measure the melting point, heat of fusion, and the number of melting peaks of the polyolefin resin using the method described above.

[0108] (2) Basis weight of spunbond nonwoven fabric: Based on the method described above, the basis weight of the spunbond nonwoven fabric was measured.

[0109] (3) Area ratio of the core component in the cross-section of the core-sheath type composite fiber in the surface portion of the spunbond nonwoven fabric: A scanning electron microscope, the "VHX-D500" manufactured by Keyence Corporation, was used, and measurements were taken using the method described above.

[0110] (4) Area ratio of the core component in the cross-section of the core-sheath type composite fiber in the other surface portion of the spunbond nonwoven fabric: A scanning electron microscope, the "VHX-D500" manufactured by Keyence Corporation, was used, and measurements were taken using the method described above.

[0111] (5) Apparent density of spunbond nonwoven fabric (g / cm³) 3 ) Based on the method described above, the apparent density of the spunbond nonwoven fabric was calculated.

[0112] (6) Tensile strength product of spunbond nonwoven fabric ((N / 50mm) / (g / m 2 )) Based on the method described above, the tensile strength-to-elongation product of the spunbond nonwoven fabric was calculated.

[0113] (7) Strong Heat Seal Three samples measuring 130 mm in the longitudinal direction and 50 mm in the width direction were cut from the spunbond nonwoven fabric at three points per meter in the width direction, with two samples at each point. Two samples were placed on top of each other with the same faces touching, and the edges were heat-sealed 30 mm from the edge using a Fuji Impulse heat sealing machine (OPL-200) to create heat-sealed samples. The bonding temperature was set to be between 100°C and 160°C, and the bonding temperature of the sample was defined as the temperature at which the average value of the heat-seal strength measured by the method described below reached its maximum. The bonding time was set to 1 second. The heat-sealed samples were mounted on a constant-speed elongation tensile testing machine with a gripping distance of 100 mm, and a load was applied at a tensile speed of 100 mm / min until the test piece peeled or broke. The maximum strength at that time was defined as the heat-seal strength. Measurements were performed on both sides of the spunbond nonwoven fabric, and if there was a difference in heat-seal strength between the two sides, the larger value was adopted as the heat-seal strength of the spunbond nonwoven fabric. Furthermore, if the adhesive portion of the sample did not peel off but other parts broke, the strength value at the time of breakage was used.

[0114] We determined that a heat seal strength of 70N / 50mm or higher was sufficient.

[0115] (8) The ratio of the strength of the double-sided heat seal In the heat seal strength measurements taken on both sides of the spunbond nonwoven fabric using the method described above, the value measured on the side with the higher heat seal strength was divided by the value measured on the side with the lower heat seal strength, and the result was rounded to two decimal places to obtain the ratio of the heat seal strengths on both sides of the spunbond nonwoven fabric.

[0116] (9) Heat sealability When performing heat sealing of spunbond nonwoven fabric using the method described above, the processability of the surface where the heat sealing strength is greatest was evaluated as follows. ○: During the heat sealing process, there was no fusion of the sample pieces to the heat sealing machine, indicating good processability. ×: During the heat sealing process, the sample piece fused to the heat sealing machine.

[0117] [Resin used] Next, we will describe in detail the resins used in the examples and comparative examples. • Polyester resin A: Dry with a moisture content of 50 ppm by mass or less, with an intrinsic viscosity (IV) of 0.65, a melting point of 260°C, and a solid density of 1.38 g / cm³. 3 Polyethylene terephthalate resin (labeled "PET" in Table 1) Polyethylene resin B: Melt flow rate (MFR) of 30 g / 10 min, melting point of 130°C, solid density of 0.955 g / cm³ 3 high-density polyethylene resin (referred to as "HDPE" in Tables 1-3) • Polyethylene resin C: Melt flow rate (MFR) of 60 g / 10 min, melting point of 118°C, solid density of 0.925 g / cm³ 3 High-density polyethylene resin (referred to as "LLDPE" in Tables 1-3) • Polypropylene resin D: Melt flow rate (MFR) of 30 g / 10 min, melting point of 160°C, solid density of 0.91 g / cm³ 3 This is a polypropylene resin (referred to as "PP" in Table 1) made of homopolymer.

[0118] [Example 1] The aforementioned polyester resin A and polyethylene resin B were melted at temperatures of 295°C and 200°C, respectively. Then, using polyester resin A as the core component and polyethylene resin B as the sheath component, the fibers were spun from the pores of a concentric core-sheath composite spinneret at a spinneret temperature (corresponding to the spinning temperature) of 295°C, a core-to-sheath mass ratio of 50:50, and an extrusion rate of 0.55 g / min per pore. After the spun yarn was cooled and solidified, it was pulled and stretched in a rectangular ejector using compressed air at an ejector pressure of 0.30 MPa. The fibers were then piled up on a moving net conveyor, with the fiber arrangement restricted by a fiber-opening plate, to collect the first fiber web. The basis weight of the first fiber web was 15 g / m². 2The average single fiber diameter was 14.3 μm. Next, a second fiber web was collected on the first fiber web in the same manner as the first fiber web, except that the mass ratio of core component to sheath component was core component:sheath component = 80:20. The basis weight of the second fiber web was 15 g / m². 2 The average single fiber diameter was 13.7 μm.

[0119] Next, using a pair of upper and lower heat embossing rolls consisting of the upper and lower rolls shown below, the material was heat-bonded under the conditions of a linear pressure of 300 N / cm and a heat bonding temperature of 130°C, resulting in a basis weight of 30 g / m². 2 A spunbond nonwoven fabric was obtained. Top roll: A metal embossed roll with a polka dot pattern, with an adhesive surface area ratio of 11%. Lower roll: Metal flat roll The evaluation results are shown in Table 1.

[0120] Note that the heat seal strength is determined by the area ratio P of the core component. C1 The result was higher when the core-sheath type composite fibers having the characteristic feature were stacked so that their surfaces were in contact with each other.

[0121] [Example 2] A spunbond nonwoven fabric was obtained using the same method as in Example 1, except that the mass ratio of core component to sheath component in the first fiber web was changed from core component:sheath component = 50:50 to core component:sheath component = 55:45, and the mass ratio of core component to sheath component in the second fiber web was changed from core component:sheath component = 80:20 to core component:sheath component = 70:30. The evaluation results are shown in Table 1.

[0122] Note that the heat seal strength is determined by the area ratio P of the core component. C1 The result was higher when the core-sheath type composite fibers having the characteristic feature were stacked so that their surfaces were in contact with each other.

[0123] [Example 3] A spunbond nonwoven fabric was obtained using the same method as in Example 1, except that the mass ratio of core component to sheath component in the first fiber web was changed from 50:50 to 40:60, and the mass ratio of core component to sheath component in the second fiber web was changed from 80:20 to 85:15. The evaluation results are shown in Table 1.

[0124] Note that the heat seal strength is determined by the area ratio P of the core component. C1 The result was higher when the core-sheath type composite fibers having the characteristic feature were stacked so that their surfaces were in contact with each other.

[0125] [Example 4] A first fiber web and a second fiber web were obtained using the same method as in Example 1.

[0126] Next, using a pair of upper and lower heat embossing rolls consisting of the upper and lower rolls shown below, the material was heat-bonded under the conditions of a linear pressure of 300 N / cm and a heat bonding temperature of 130°C, resulting in a basis weight of 30 g / m². 2 A spunbond nonwoven fabric was obtained. Top roll: A metal embossed roll with a polka dot pattern, with an adhesive surface area of ​​60%. Lower roll: Metal flat roll The evaluation results are shown in Table 1.

[0127] Note that the heat seal strength is determined by the area ratio P of the core component. C1 The result was higher when the core-sheath type composite fibers having the characteristic feature were stacked so that their surfaces were in contact with each other.

[0128] [Example 5] A first fiber web was formed using the same method as in Example 1, except that polypropylene resin D was used instead of polyethylene resin B, and the melting temperature was set to 240°C. The basis weight of the first fiber web was 15 g / m². 2 The average single fiber diameter was 14.3 μm.

[0129] A second fiber web was formed on the first fiber web described above, using the same method as in Example 1, except that polypropylene resin D was used instead of polyethylene resin B, and the melting temperature was set to 240°C. The basis weight of the second fiber web was 15 g / m². 2 The average single fiber diameter was 14.3 μm.

[0130] Next, the bonding was performed using the same method as in Example 1, resulting in a basis weight of 30 g / m². 2 A spunbond nonwoven fabric was obtained. The evaluation results are shown in Table 1.

[0131] Note that the heat seal strength is determined by the area ratio P of the core component. C1 The result was higher when the core-sheath type composite fibers having the characteristic feature were stacked so that their surfaces were in contact with each other.

[0132] [Comparative Example 1] The first fiber web was collected using the same method as in Example 1. The basis weight of the fiber web was 30 g / m². 2 The average single fiber diameter was 14.3 μm.

[0133] Next, the fiber web was heat-bonded using the same method as in Example 1, resulting in a basis weight of 30 g / m². 2 A spunbond nonwoven fabric was obtained. The evaluation results are shown in Table 1.

[0134] [Comparative Example 2] The first fiber web was collected using the same method as in Example 1, except that polyethylene resin C was used instead of polyethylene resin B. The basis weight of the fiber web was 15 g / m². 2 The average single fiber diameter was 14.3 μm.

[0135] A second fiber web was formed on the first fiber web using the same method as in Example 1. The basis weight of the second fiber web was 15 g / m². 2 The average single fiber diameter was 13.7 μm.

[0136] Next, the fiber web was heat-bonded using the same method as in Example 1, resulting in a basis weight of 30 g / m². 2Table 1 shows the evaluation results obtained for the spunbond nonwoven fabric.

[0137] Note that the heat seal strength is determined by the area ratio P of the core component. C1 The result was higher when the core-sheath type composite fibers having the characteristic feature were stacked so that their surfaces were in contact with each other.

[0138] [Comparative Example 3] A spunbond nonwoven fabric was obtained using the same method as in Example 1, except that the mass ratio of core component to sheath component in the first fiber web was changed from 50:50 to 80:20, and the mass ratio of core component to sheath component in the second fiber web was changed from 80:20 to 90:10. The evaluation results are shown in Table 1.

[0139] Note that the heat seal strength is determined by the area ratio P of the core component. C1 The result was higher when the core-sheath type composite fibers having the characteristic feature were stacked so that their surfaces were in contact with each other.

[0140] [Comparative Example 4] A spunbond nonwoven fabric was obtained using the same method as in Example 1, except that the mass ratio of core component to sheath component in the first fiber web was changed from 50:50 to 30:70, and the mass ratio of core component to sheath component in the second fiber web was changed from 80:20 to 95:5. The evaluation results are shown in Table 1.

[0141] Note that the heat seal strength is determined by the area ratio P of the core component. C1 The result was higher when the core-sheath type composite fibers having the characteristic feature were stacked so that their surfaces were in contact with each other.

[0142] [Table 1]

[0143] As shown in Table 1, the spunbond nonwoven fabrics of Examples 1 to 5 exhibited sufficient heat-sealability and strength. On the other hand, the spunbond nonwoven fabric of Comparative Example 1 exhibited poor heat-sealability, with the sample piece fusing to the heat-sealing machine during heat-sealing. Furthermore, the spunbond nonwoven fabrics of Comparative Examples 2 and 4 fractured at an early stage during heat-seal strength measurement, indicating they lacked sufficient heat-seal strength. The spunbond nonwoven fabric of Comparative Example 3 also lacked sufficient heat-seal strength.

Claims

1. A spunbond nonwoven fabric composed of core-sheath type composite fibers, The core component of the aforementioned core-sheath type composite fiber is a thermoplastic resin A mainly composed of polyester resin, The sheath component of the core-sheath type composite fiber is a thermoplastic resin B mainly composed of a polyolefin resin, When differential scanning calorimetry was performed on the aforementioned spunbond nonwoven fabric, a single melting peak originating from the polyolefin resin was observed. Furthermore, a spunbond nonwoven fabric that satisfies the following equations 1 and 2. 0.10≦P C1 ≦0.70 ・・・(Equation 1) 0.10≦P C2 -P C1 ≦0.55 ・・・(Equation 2) Here, P C1 This is the area ratio (unitless) of the core component in the cross-section of the core-sheath type composite fiber in the portion of one surface side of the spunbond nonwoven fabric, P C2 This is the area ratio (unitless) of the core component in the cross-section of the core-sheath type composite fiber in the other surface portion of the spunbond nonwoven fabric.

2. The aforementioned polyester resin is polyethylene terephthalate resin. The aforementioned polyolefin resin is polyethylene resin. When differential scanning calorimetry is performed on the aforementioned spunbond nonwoven fabric, the difference between the temperature of the melting peak with the largest heat of fusion and the temperature of the melting peak with the second largest heat of fusion is between 50°C and 250°C. The spunbond nonwoven fabric according to claim 1.

3. The apparent density of the spunbond nonwoven fabric is 0.05 g / cm³. 3 0.90g / cm or more 3 The following is: The spunbond nonwoven fabric according to claim 1 or 2.

4. The product of tensile strength and elongation per basis weight in the longitudinal direction of the spunbond nonwoven fabric is 1.0 (N / 50 mm) / (g / m 2 ) or more and 4.0 (N / 50 mm) / (g / m 2 ) or less. The spunbond nonwoven fabric according to claim 1 or 2.

5. A method for producing a spunbond nonwoven fabric according to claim 1 or 2, A step of forming a first fiber web composed of a first core-sheath type composite fiber, wherein the core component is a thermoplastic resin A mainly composed of polyester resin, and the sheath component is a thermoplastic resin B mainly composed of polyolefin resin; A step of forming a laminated web by forming a second fiber web on the first fiber web, the second fiber web being composed of a second core-sheath type composite fiber, the second core-sheath type composite fiber being composed of a thermoplastic resin A whose core component is mainly composed of a polyester resin and the third core-sheath type composite fiber being composed of a thermoplastic resin B whose sheath component is mainly composed of a polyolefin resin, A step of heat-sealing the laminated web with a pair of heat rolls, Includes, A method for producing a spunbond nonwoven fabric that satisfies the following equations 1 and 2. 0.10≦P C1 ≦0.70 ・・・(Equation 1) 0.10≦P C2 -P C1 ≦0.55 ・・・(Equation 2) Here, P C1 This is the area ratio (unitless) of the core component in the cross-section of the core-sheath type composite fiber in the portion of one surface side of the spunbond nonwoven fabric, P C2 This is the area ratio (unitless) of the core component in the cross-section of the core-sheath type composite fiber in the other surface portion of the spunbond nonwoven fabric.

6. The aforementioned polyolefin resin is a polyethylene resin, The solid density of the polyethylene resin is 0.935 g / cm³. 3 0.970g / cm or more 3 The method for producing a spunbond nonwoven fabric according to claim 5 is as follows:

7. A packaging material comprising the spunbond nonwoven fabric according to claim 1 or 2.

Citation Information

Patent Citations

  • Heat-sealing nonwoven fabric

    JP2007321311A